2017
DOI: 10.5897/ajmr2017.8525
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate solubilizing fungi isolated and characterized from Teff rhizosphere soil collected from North Showa zone, Ethiopia

Abstract: Phosphorus is one of the major bio elements limiting agricultural production. About 95 to 99% phosphorus in agricultural soil is unavailable form for plant growth. Phosphate solubilizing microorganisms can increase soil phosphate availability. This study was aimed to identify and evaluate phosphate solubilizing fungi from Teff rhizosphere soil. Fungi were identified using lactophenol cotton blue staining confirmation and Biolog Microstation identification system. At 15 days incubation, T. beigelii B and R. aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 31 publications
(28 reference statements)
0
3
0
1
Order By: Relevance
“…Free living fungi are also able to increase nutrient availability. A strain of Trichoderma harzianum (Altomare et al, 1999), and other fungi such as Trichosporon beigelii , Phichia norvegensis , Cryptococcus albidus var aerius , as well as Penicillium bilaii (Kucey, 1987; Cunningham and Kuiack, 1992; Gizaw et al, 2017) have shown inorganic phosphate and other mineral solubilization capabilities. In our results, we observed that many of the 50 most abundant rhizospheric fungal OTUs were related to Phoma , Fusarium , Penicillium , Eupenicillium , and Trichoderma species (Supplementary Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Free living fungi are also able to increase nutrient availability. A strain of Trichoderma harzianum (Altomare et al, 1999), and other fungi such as Trichosporon beigelii , Phichia norvegensis , Cryptococcus albidus var aerius , as well as Penicillium bilaii (Kucey, 1987; Cunningham and Kuiack, 1992; Gizaw et al, 2017) have shown inorganic phosphate and other mineral solubilization capabilities. In our results, we observed that many of the 50 most abundant rhizospheric fungal OTUs were related to Phoma , Fusarium , Penicillium , Eupenicillium , and Trichoderma species (Supplementary Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Among the fungi, Aspergillus sp., Penicillium sp. and Schwanniomyces occidentalis are considered to be the predominant members that convert insoluble inorganic phosphate in soil into soluble plant-usable forms (Gizaw et al 2017;Alori et al 2017). Earlier, culture-dependent approaches revealed that Bacillus subtilis and Aspergillus niger were most dominant in P-de cient acidic soils under tea cultivation (Bhattacharyya and Sarmah 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Jordan, United Kingdom [11] Mycobacterium confuentis Ethiopia [55] Neosartorya fsheri var. fscheri Ethiopia [58] Ochrobactrum pseudogrignonense…”
Section: Mortierella Nanamentioning
confidence: 99%